Moral Philosophy and Publication Ethics (LIS TODAY, 2021)
Abstract: Moral philosophy is a branch of philosophy that can help us to examine and lead an  ethical life. Ethics is a branch of philosophy that “involves systematizing, defending and  recommending concepts of right and wrong behaviour”. Ethical subjects can be partitioned into four  sections proposals are meta-ethics, descriptive ethics, normative ethics and applied ethics. Most of  the ethical standards remain consistent with time and they do not change over the period. There have  been a few prominent instances of plagiarism over the most recent couple of years. Institutions must  take the responsibility for ensuring academic standards and for emphasising, to both students and  faculty, the importance of maintaining the highest standards of integrity in academic research”.  COPE(The Committee on Publication Ethics) is focused on teaching and supporting editors,  publishers and those associated with publication ethics with the point of moving the way of culture of  publication towards one where moral practices turns into an ordinary aspect of the publishing  society. WAME is a philanthropic deliberate relationship of editors of companion checked on medical  journals from nations all through the world who look to encourage worldwide participation among  and training of medical journal editors. Literary theft recognition instruments for e-learning  Professionals recognize a job well done.
Keywords: Moral philosophy; Ethics; Scientific misconduct; FFP; Redundant Publications; Duplicate and overlapping publications; Salami Slicing; Publication Ethics; Professional Ethics; COPE; WAME